2015
DOI: 10.1080/21655979.2014.996430
|View full text |Cite
|
Sign up to set email alerts
|

Kiwi fruit (Actinidia chinensis) quality determination based on surface acoustic wave resonator combined with electronic nose

Abstract: Keywords: electronic nose, frequency, Kiwi fruit quality, signal-to-noise ratio, surface acoustic wave resonatorIn this study, electronic nose (EN) combined with a 433 MHz surface acoustic wave resonator (SAWR) was used to determine Kiwi fruit quality under 12-day storage. EN responses to Kiwi samples were measured and analyzed by principal component analysis (PCA) and stochastic resonance (SR) methods. SAWR frequency eigen values were also measured to predict freshness. Kiwi fruit sample's weight loss index a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Grouping fruit by overall ripeness was more reliable, and this method has also been adopted in studies on the banana [16], mango [17] and peach [36]. Previously, Liu et al [24] used a MOS E-nose system to detect the quality of kiwifruit and classified the samples at different storage days. Seven groups with 5 replicates were poorly classified, which is similar to the results presented in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grouping fruit by overall ripeness was more reliable, and this method has also been adopted in studies on the banana [16], mango [17] and peach [36]. Previously, Liu et al [24] used a MOS E-nose system to detect the quality of kiwifruit and classified the samples at different storage days. Seven groups with 5 replicates were poorly classified, which is similar to the results presented in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [24] used a MOS E-nose system to detect the quality of kiwifruit. They mainly focused on the qualitative discrimination of kiwifruit at different storage times, but no other research has been reported for the further quantitative prediction of the internal quality of kiwifruit by E-nose.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and chemical method including firmness and microbial are used effectively to determine the quality condition of kiwifruit. Some new instrument detection methods with accurate analysis ability such as GC, GC-MS, HPLC, UPLC-QqQ-MS/MS, and electronic nose combined with surface acoustic wave resonator are developed for the fruit and its products quality rapid analysis (Kvesitadze et al, 2001; Montefiori et al, 2005; Liu and Hui, 2015; Jiao et al, 2019). As to radix A. chinensis , the systematical method like UPLC-TOF/MS and UPLC-QqQ/MS is commonly applied to quality evaluation and active components analysis for A. chinensis (Zhao et al, 2014).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…China is the leading producer of kiwifruit, ahead of all countries (Guo et al, 2017a), especially in the subtropical provinces of Taiwan, Guangdong, Guangxi Zhuang Autonomous Region, and Yunnan. Kiwifruit has many benefits for the human body, for the rich of vitamin C, organic acids, tannins, carbohydrates, pectin, essential amino acids, trace elements, inositol and lutein (Wei & Guohua, 2015;Satpal et al, 2021). Studies have shown that kiwifruit has many pharmacological properties, including antioxidant, hypoglycemic (Tyagi, 2015), constipation treatment (El Azab & Mostafa, 2022) and protecting the liver (Satpal et al, 2021), and so on.…”
Section: Introductionmentioning
confidence: 99%